CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND VALUE OF LISTED OIL AND GAS COMPANIES IN NIGERIA: THE MODERATING EFFECT OF FOREIGN OWNERSHIP - Kantudu, Aliyu Sulaiman; Dandago, Kabiru Isa; Yusuf, Abubakar; Maigoshi, Zaharaddeen Salisu; Sulaiman, Bashir Ali (Australian Finance & Banking Review, 2023)
This study examines the moderating effect of foreign ownership on the relationship between corporate social responsibility disclosure and the value of listed oil and gas companies in Nigeria. This study adopted an explanatory research design to achieve this objective using secondary data collected from annual reports and accounts of the sampled companies for four years (2018-2021). The study employs multiple regression using panel-corrected standard error (PCSE) to analyze data for the study. Findings indicate that corporate social responsibility disclosure has a positive significant impact on firm value. Results also revealed that foreign ownership has a positive but insignificant impact on firm value. Furthermore, on the interaction effect of foreign ownership on the relationship between corporate social responsibility disclosure and firm value, the result indicates that foreign ownership has moderated the relationship between corporate social responsibility disclosure and the value of listed oil and gas companies in Nigeria by strengthening the existing relationship. The findings of this study encourage more investment from foreign investors to increase the disclosure of CSR to enhance the value of listed oil and gas companies in Nigeria. Finally, the study recommends that the management of listed oil and gas companies should diversify to attract more foreign investors to improve the value of their companies.JEL Classification Codes: O16.